Who Are Godwin and Hopwood? - Mojca Smode Cvitanović (Prostor)
The monograph provides a precise section through the work of the practice founded in Lagos in 1955 and active throughout the decades. Within the context of pre- and post-independence Nigeria, its relevance is examined in terms of social role and climate considerations. Set according to the typologies of the selected works, the content of the book provides a valuable source of reference, with emphasis on the climate performability of buildings.